2017
DOI: 10.1002/app.45346
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and performance evaluation of PES/EDA‐functionalized TiO2 mixed matrix membranes for CO2/CH4 separation

Abstract: Poor adhesion between hydrophobic polymers and hydrophilic inorganic fillers is a challenge that encumbers a high separation performance of mixed matrix membrane (MMM). In this study, Titanium(IV) oxide (TiO2) nanoparticles were functionalized using ethylenediamine (EDA) before embedment in poly(ether sulfone) (PES) polymer matrix. MMMs were synthesized through dry phase inversion technique. Membranes morphology and nanoparticles dispersion was drastically enhanced posterior amine modification indicating an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Likewise, some molecules such as ethylenediamine (EDA) or L-methionine can also be added to enhance the interfacial miscibility between TiO 2 nanoparticles and PES via the H-bonding effect of -NH 2 or -COOH. 33 In Azadeh et al' research, they synthesized a Polyaniline (PANi) shell on the surface of TiO 2 nanoparticles to improve the dispersion of fillers in the PES substrate through p-p conjugation interaction, 34 (donor atom) and -SO 3 À (acceptor atom) was smaller than that of -SO providing stronger interactions for combination (Fig. 1b).…”
Section: Pes Compositesmentioning
confidence: 99%
“…Likewise, some molecules such as ethylenediamine (EDA) or L-methionine can also be added to enhance the interfacial miscibility between TiO 2 nanoparticles and PES via the H-bonding effect of -NH 2 or -COOH. 33 In Azadeh et al' research, they synthesized a Polyaniline (PANi) shell on the surface of TiO 2 nanoparticles to improve the dispersion of fillers in the PES substrate through p-p conjugation interaction, 34 (donor atom) and -SO 3 À (acceptor atom) was smaller than that of -SO providing stronger interactions for combination (Fig. 1b).…”
Section: Pes Compositesmentioning
confidence: 99%
“…Finally, the remaining polymer solution is poured into the “primed” solution under continuous stirring. This strategy is applicable to various fillers, such as zeolite, TiO 2 , mesoporous silica (MSS), and MOFs. ,, Koros et al pioneered to investigate the influence of a membrane preparation protocol on final membrane microstructures by utilizing a zeolite 4A-poly­(vinyl acetate) (PVAc) system . They found that MMMs prepared from direct polymer–filler mixing showed a “sieve-in-a-cage” morphology owing to the poor contact between the filler and the polymer on the interface.…”
Section: Factors Influencing the Performance Of Mmmsmentioning
confidence: 99%
“…MMMs are heterogeneous membranes with the combination of inorganic materials, reinforced in the continuous polymeric matrix. Researchers reported extensive work on MMMs [71][72][73][74][75][76]. Powell et al reported [77] that the addition of nanoparticles mainly can contribute three effects to the membrane permeability, i.e., they can act as molecular sieves to change the permeability, they can alter the membrane matrix structure to enhance the permeability, and they can also work as a wall to decrease the permeability.…”
Section: Mixed-matrix Membranesmentioning
confidence: 99%